TO THE STUDY OF WAKE VORTEX BEHIND THE AIRBUS-380 CHARACTERISTICS AT TAKEOFF AND LANDING - A. I. Zhelannikov (Научный вестник МГТУ ГА)
Every year new aircraft emerge in civil aviation (HA). The wide-body A-380 aircraft with a take-off weight of up to 560 t has come to operation recently. The wake vortex behind such plane poses a real threat for other planes. Such wake is especially dangerous during weak cross wind at take off and landing.Vortex wake behind the A 380 plane characteristics research using the developed copmuting software has been executed in this article. Design-software complex includes two mathematical models: the mathematical model of the close Wake vortex and the mathematical model of the distant Wake vortex. These mathematical models are based on the vortex method. A mathematical model of the close Wake vortex is based on the analytical-experimental approach. At cruising flight regimes it is a four vortex system Wake vortex, and at takeoff and landing regimes it is - six-or eight-vortex system. A mathematical model of the far Wake vortex is based on the exact solution of the Helmholtz equations. This allows taking into account the vortex diffusion and dissipation over time. The influence of the axial velocity in the mathematical model of the distant Wake vortex is given by placing it in the center of the vortex flow. Its intensity is found from the experimental data. Calculated fields are per-turbed velocities for the A-380 aircraft.Fields of the indignant speeds at a light cross wind of 0.5 m/s ÷ 1.5 m/s in varioustime points are presented. The moments at which there is a wing vortex lag of the A-380 plane over very center are runwayare shown. Calculation of aerodynamic characteristics of the MC-21-400 plane in the vortex trace of the A-380 plane is executed. It is shown when the MC-21-400 plane gets in to the center of a wings vortex, the arising moments of the roll are not parried.